2011
DOI: 10.1248/bpb.34.1065
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Nucleosomal Binding Domain 2 Protein Protects Bladder Epithelial Cells from Klebsiella pneumoniae Invasion

Abstract: Due to the predominance of multiple-antibiotic-resistant Klebsiella pneumoniae strains, the search for new approaches for the prevention of K. pneumoniae infections is now under intensive investigation. The objective of the present study was to investigate the effects of high mobility group nucleosomal binding domain 2 (HMGN2) protein, which acts on the bladder epithelial cells T 24, on the invasion of K. pneumoniae 03183 and explore its possible mechanisms. Pretreatment with HMGN2 significantly reduced K. pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In the K. pneumoniae and BSA groups, F-actin expression and stress fibers were increased and the average fluorescence intensity of F-actin was significantly increased as compared with that in the PBS group, which indicated that following infection, polymerized F-actin was enhanced. Of note, in the HMGN2 group, F-actin expression and average fluorescence intensity of F-actin were decreased, which indicated that HMGN2 inhibited K. pneumoniae 03183 invasion of lung cells directly through reducing the polymerization of F-actin, which is consistent with previous studies by our group (24,25).…”
Section: A B Csupporting
confidence: 91%
See 2 more Smart Citations
“…In the K. pneumoniae and BSA groups, F-actin expression and stress fibers were increased and the average fluorescence intensity of F-actin was significantly increased as compared with that in the PBS group, which indicated that following infection, polymerized F-actin was enhanced. Of note, in the HMGN2 group, F-actin expression and average fluorescence intensity of F-actin were decreased, which indicated that HMGN2 inhibited K. pneumoniae 03183 invasion of lung cells directly through reducing the polymerization of F-actin, which is consistent with previous studies by our group (24,25).…”
Section: A B Csupporting
confidence: 91%
“…indicated that it inhibited the invasion of K. pneumoniae 03183 neither by inhibiting the growth of bacteria nor by inhibiting the physical progress of pre-treatment with protein (24,25).…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…And we also showed that HMGN2 is a novel antimicrobial molecule, having a potent antimicrobial activity against Escherichia coli ML-35p, hepatitis B virus in vitro (Feng et al, 2005;. The antimicrobial effects of HMGN2 on Klebsiella pneumoniae internalization and invasion in bladder epithelial cells Cao et al, 2011), and in E. coli and Pseudomonas aeruginosa have been reported (Feng et al, 2005). However, the antibacterial mechanism of HMGN2 has not been fully elucidated.…”
mentioning
confidence: 89%
“…31 Otherwise, we found HMGN2 participated in MAPK signalling through activating ERK1/2 and P38, and regulating autophagy by AMPK pathway to reduce Uropathogenic Escherichia coli internalization of bladder epithelial cells. 32 However, the role of HMGN2 for regulating the anti-non-tuberculous mycobacteria innate immunity of macrophage is still largely unknown.…”
Section: Hmgn2mentioning
confidence: 99%